CHARACTERISTICS OF DEMOGRAPHIC DEVELOPMENT OF FERGANA VALLEY (Scientific journal of the Fergana State University, 2023)
This article reflects the development of demographic processes in Fergana Valley during the years of independence, the age and sex composition of the population, the level of employment and the demographic potential of cities and villages in the valley.